광선 각화증 환자에게서 5-Aminolevulinic Acid를 이용한 광역동 치료 후 나타난 광회춘 효과: 조직학적 분석 - 박민영 (The Graduate School, Ajou University, 2009)
Background: Repeated exposure to ultraviolet radiation from the sun results in premature photoaging. Photodamaged skin is histologically characterized by reduced collagen synthesis, increased collagen destruction, and accumulation of abnormal elastotic material in the dermis. Photodynamic therapy (PDT) is one of many treatment options available for photoaging; it has been shown to be effective, whereas the data on most other studies is based on clinical observation. Objectives: I investigated whether 5-aminolevulinic acid (ALA)-PDT induced histological changes suggesting photorejuvenation. Materials and Methods: Fourteen patients with one to three actinic keratosis on the face were treated twice with ALA-PDT using a 1200W metal halogen lamp at one month intervals. Skin biopsy before and one month after the PDT was performed. Twenty five pairs of specimens were obtained. I examined the specimens with routine and immunohistochemical staining and evaluated the parameters associated with photoaging using image analysis. Results: After ALA-PDT, the mean epidermis thickness and inflammatory infiltrate in the dermis were reduced. The total collagen volume in the dermis was significantly increased with expression of type I and III procollagen. The level of transforming growth factor ？] and transforming growth factor ？？ type II receptors were also increased. The elastotic material with co-localizing fibrilline-1 and tropoelastin expression in the dermis tended to decrease after treatment. The expression of matrix metalloproteinases -1, -3, and -12 was also decreased. Conclusion: The histological evidence showed beneficial effects of ALA-PDT for photodamaged skin. Further controlled split-face studies are required to determine the precise mechanism underlying the effects of ALA-PDT on photoaging.
학위논문(석사)--아주대학교 일반대학원 :의학과,2009. 2
Keywords: Photodynamic therapy; Photorejuvenation; Histological changes